The worldly wisdom of A. Schopenhauer - Rubanau, Anatoly V. (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
The views of A. Schopenhauer on the concept «worldly wisdom» are presented. It is revealed that the philosopher contrary to his metaphysical-ethical point of view considers this term as an art of spending life as pleasantly and happily as possible. It is shown that a person’s happy life is connected with who he is as a person, as well as with his attitude to property and the opinion of other people. Two main factors that hinder the achievement of happiness (pain and boredom) are named. The first factor correlates with the state of health, the second factor correlates with inner emptiness. It is pointed out that overcoming the inner emptiness consists in the formation of spiritual needs thanks to which a person’s life is filled with meaning. Practical advice of A. Schopenhauer on achieving happiness is given.